2021
DOI: 10.3892/mmr.2021.12505
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑200c‑3p suppresses intervertebral disc degeneration by targeting RAP2C/ERK signaling

Abstract: Intervertebral disc degeneration (IDD) is a major cause of lower back pain. The high morbidity associated with this disease diminishes the quality of life of those who are affected. MicroRNAs (miRs) play crucial roles in various diseases, including IDD. However, the mechanism via which miR-200c-3p plays a role in the development of IDD remains unknown. The present study aimed to investigate the effect of miR-200c-3p on the progression of IDD and the underlying mechanism. The expression level of miR-200c-3p was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…56 Another study showed that LPS treatment could dramatically enhance the expression of TNF-α, IL-6, and other inflammatory factors in NP cells by down-regulating microRNA-200C-3p . 57 IL-10 is a cytokine with anti-inflammatory properties that plays a central role during infection by limiting the immune response to pathogens and thereby preventing damage to the host. 58 The above literature substantiates that activation of pyroptosis in IVDD tissue induces inflammatory responses and aggravates disc degeneration by stimulating various cytokines, including IL-1β, IL-6, IL-8, IL-18, etc .…”
Section: Biological Roles Of Pyroptosis Of Different Ivd Cells On The...mentioning
confidence: 99%
“…56 Another study showed that LPS treatment could dramatically enhance the expression of TNF-α, IL-6, and other inflammatory factors in NP cells by down-regulating microRNA-200C-3p . 57 IL-10 is a cytokine with anti-inflammatory properties that plays a central role during infection by limiting the immune response to pathogens and thereby preventing damage to the host. 58 The above literature substantiates that activation of pyroptosis in IVDD tissue induces inflammatory responses and aggravates disc degeneration by stimulating various cytokines, including IL-1β, IL-6, IL-8, IL-18, etc .…”
Section: Biological Roles Of Pyroptosis Of Different Ivd Cells On The...mentioning
confidence: 99%